Formulation and evaluation of chitosan-based long-acting injectable hydrogel for PEGylated melphalan conjugate. (13th May 2014) - Alexander, Amit; , Ajazuddin; Khan, Junaid; Saraf, Swarnlata; Saraf, Shailendra
Abstract: Objectives: In this study, we have used melphalan (ML) as a model drug, used extensively for the treatment of breast cancer. Due to its remarkable haemolytic activity, clinical application of this drug is limited. Methods: We incorporated the two synthesized PEGylated melphalan conjugates, viz. MLPEG 2000 and MLPEG 5000, separately into the medium molecular weight chitosan (CS)-based smart thermoreversible in-situ forming injectable hydrogel. Prepared hydrogels were evaluated for gelation time, rheological behaviour, drug release and stability. Key findings: Although PEGylated melphalan shows significant increase in aqueous solubility and decrease in haemolytic activity, it was loaded to hydrogel to improve dose frequency and local effect. Hydrogel comprising CS (3.22%, w/v) and glycerophosphate disodium salt (GP) (16%, w/v) showed consistent gelation time and retard the release of drug without compromising its stability. To underline the role of GP, conjugates were loaded into CS solution with and without the GP. Remarkably, absence of GP results in rapid initial burst with nearly complete drug release within 50 h, while addition of GP exhibited drug release up to 100 h. Conclusions: Thus, this study highlighted the role of CS/GP thermoreversible injectable hydrogel for successful loading of PEGylated melphalan.